Synthesis, complexation, spectral and antimicrobial study of some novel 5-bromo-2-fluorobenzaldehydeoxime and semicarbazone under ultrasonic irradiation - Emayavaramban, M.; Kumar, K.; Mani, P.; Prabhakaran, B.; Muthuvel, A. (International Journal of Advanced Chemistry, 2014)
In this newly approached method a novel series of Transition metal complexes were synthesized by ultrasonic irradation. The reaction of 5-bromo-2-fluorobenzaldehydeoxime (L1OX) and 5-bromo-2-fluorobenzaldehydesenicarbazone (L2SC) by reaction with Cu(II) and pd(II)chloride salts. The complexes were characterized by elemental analysis, Ultraviolet, Infrared and NMR spectral studies. The antimicrobial activities of the ligand and its metal complexes were estimated.   Keywords: Substituted Benz aldehyde, metals, complexes, antibacterial and antifungal activity.